Availability of malaria diagnostic tests, anti-malarial drugs, and the correctness of treatment: a systematic review and meta-analysis - Hosein Azizi; Elham Davtalab Esmaeili; Fariba Abbasi (Malaria Journal, 2023)
Abstract Background Health facilities’ availability of malaria diagnostic tests and anti-malarial drugs (AMDs), and the correctness of treatment are critical for the appropriate case management, and malaria surveillance programs. It is also reliable evidence for malaria elimination certification in low-transmission settings. This meta-analysis aimed to estimate summary proportions for the availability of malaria diagnostic tests, AMDs, and the correctness of treatment. Methods The Web of Science, Scopus, Medline, Embase, and Malaria Journal were systematically searched up to 30th January 2023. The study searched any records reporting the availability of diagnostic tests and AMDs and the correctness of malaria treatment. Eligibility and risk of bias assessment of studies were conducted independently in a blinded way by two reviewers. For the pooling of studies, meta-analysis using random effects model were carried out to estimate summary proportions of the availability of diagnostic tests, AMDs, and correctness of malaria treatment. Results A total of 18 studies, incorporating 7,429 health facilities, 9,745 health workers, 41,856 febrile patients, and 15,398 malaria patients, and no study in low malaria transmission areas, were identified. The pooled proportion of the availability of malaria diagnostic tests, and the first-line AMDs in health facilities was 76% (95% CI 67–84); and 83% (95% CI 79–87), respectively. A pooled meta-analysis using random effects indicates the overall proportion of the correctness of malaria treatment 62% (95% CI 54–69). The appropriate malaria treatment was improved over time from 2009 to 2023. In the sub-group analysis, the correctness of treatment proportion was 53% (95% CI 50–63) for non-physicians health workers and 69% (95% CI 55–84) for physicians. Conclusion Findings of this review indicated that the correctness of malaria treatment and the availability of AMDs and diagnostic tests need improving to progress the malaria elimination stage.